ORAL CAVITY MESENCHYMAL STEM CELLS: ORIGIN, SURFACE MARKERS, AND REGENERATIVE POTENTIAL - Xisto Braga Cavalcanti, Marcos Fernando; Matos , Ícaro Gabriel Teles Pacheco De; Costa , Ala Gustavo De Andrade; Brito, Gianny Dominicci Batista; Diomede, Francesca; Maria , Durvanei Augusto (Brazilian Journal of Implantology and Health Sciences, 2025)
Objective: This review investigated the origin, surface markers, and the regenerative potential of mesenchymal stem cells from the oral cavity. Background: This review addresses the regenerative potential of mesenchymal stem cells (MSCs) from the oral cavity, including the formation of dental tissues, pulp tissue, and periodontal tissues, and a whole bio-hybrid tooth composed of dentin, cementum, periodontal ligament, and alveolar bone. Teeth sequelae can be caused by cavities, trauma, or infection, leading to endodontic problems, periodontal disease, and tooth loss. Method: This work selected 67 articles revising the literature using PubMed and Google Scholar, these stem cells were separated according to their origin, surface markers, and regenerative potential. Conclusion: Although a lot of research and clinical trials have to be done to validate clinical use of this knowledge in humans, this field is vast and promising, bringing light to new therapies that can solve clinical problems and reformulate dental treatments shortly.